STATISTICAL ASSESSMENT OF THE ROLE OF INDUSTRY AND OTHER SECTORS IN THE DEVELOPMENT OF THE ECONOMY OF UZBEKISTAN - Ayubjanov Abbas Khasilovich (Scholar Express Journals, 2023)
The article analyzes the place and role of industries in ensuring economic development, the share of industries in the production of industrial products and their dynamics based on international classifications and outlines the directions for further strategic development of the industry.
Keywords: products; sector; GDP